Relationship Between the Role of Christian Religious Education Teachers According to Titus 2:6-8 And the Character Development of High School Students in Loa Janan Ilir District During The 2023/2024 Academic Year - Bali, Henita Tangdi; Yulia, Tantri; Rombe, Eni (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The study aims to explore the relationship between the role of the Christian Teacher of Education (PAK) according to Titus 2:6-8 and the character development of high school students in the Loa Janan Ilir region for the academic year 2023/2024. Using the method of correlation analysis, the findings showed a positive correlationship between the role of PAK teacher and student character development, even though the correspondence was low with a Pearson correlative coefficient of 0.249. The results of the analysis also indicated that only a small part of the variability in student character development can be attributed to the role of PAK teacher, with a determination coefficient (ry2) of 6.2%. The study also highlighted that the majority of variabilities in the character development of students (93.8%) are influenced by factors outside the scope of the study. However, the level of significance of the correlation factor found (0.05) indicates that there is a statistically significant relationship between the teacher's role and the student's character development. Thus, the study provides important insights into the role of PAK Teachers in shaping the character of high school students, while emphasizing the importance of considering other external factors that contribute to student character development